Teaching adults - Hayes, Amanda (Essential FE toolkit series., 2006)
This is a survival guide to teaching adults in FE. Amanda Hayes places students at the heart of teaching and learning and provides readers with practical strategies to help them create a stimulating and effective learning environment in college, workplace and community venues.€ €. A wide range of issues are covered including: catering for different learning styles, managing learner's expectations, promoting diversity and social inclusion, learning in the workplace and dealing with punctuality and retention. €. A variety of approaches are presented from which the reader can devel.